EL RETO DE REGULAR UN PERFIL NO PROFESIONALIZADO: MICROINSTAGRAMERS DE MODA - Ddo. Ángela AGULLEIRO PRATS,Dra. Susana MIQUEL-SEGARRA,Dra. Irene GARCÍA MEDINA,Dra. Zahaira Fabiola GONZÁLEZ ROMO, (Fonseca, Journal of Communication, 2023)
At present, the lack of specific regulation and the ambiguity of the Spanish legislation mean that many instagramers do not feel obliged to mention that the content they publish contains adverts. In countries such as the United States and the United Kingdom, this is strongly regulated. Regulation is beginning in Spain via the «Autocontrol de la publicidad»association. This study analyzes how a group of Spanish fashion micro-influencers adopt the current regulation re-quirements in their publications on Instagram. In our study, we have been able to observe that the fashion micro-instagramers do not break the law as it is only required that the public is informed that «they are in front of an advertis-ing piece.The word ‘advert’ does not need to appear in the content. (IAB Spain, 2016).